Crediting-Related Activities Under the PMR : Status and Support for Implementation - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
The objectives of this study are threefold: a) to review and compare the PMR crediting-related activities presented in MRPs; b) to assess whether and how these crediting-related activities can stimulate scaled-up mitigation by creating a domestic environment (technical, regulatory and institutional) that can support a range of climate policies; and c) to identify opportunities for the PMR to consolidate the support.